2019
DOI: 10.1002/joc.6100
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of La Niña decay and the corresponding spring and summer precipitation anomalies over eastern China

Abstract: The present study investigates the diversity of the La Niña decaying phase and the corresponding spring and summer precipitation anomalies over the eastern China. Based on the differences in sea surface temperature anomaly (SSTA) evolution during the La Niña decaying phase, 18 La Niña events in the period 1961–2016 are classified into three types—namely, the “persistent type” (P‐type), the “re‐intensified type” (R‐type), and the “fast‐decay type” (F‐type). Precipitation responses over eastern China during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Dust aerosol arises mainly from arid desert regions and exerts a significant influence on global climate and energy budgets (e.g., Chen et al, ; Ge et al, ; Hu et al, ; Huang et al, ). The emission of dust aerosol can not only change the radiative budget of the Earth system through absorbing and scattering solar radiation directly but also influence the cloud microphysical processes indirectly, and even the ecosystems at regional and global scales (Chen et al, ; Degobbi et al, ; DeMott et al, ; Jickells et al, ; Mahowald et al, ; Miller et al, ; Rosenfeld & Nirel, ). East Asia is a major source of dust aerosol as there are several deserts located in northwestern China and Mongolia that contribute a large amount of dust particles to the global dust mass loading (e.g., Chen et al, ; Guan et al, ; Hara et al, ; Huang et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Dust aerosol arises mainly from arid desert regions and exerts a significant influence on global climate and energy budgets (e.g., Chen et al, ; Ge et al, ; Hu et al, ; Huang et al, ). The emission of dust aerosol can not only change the radiative budget of the Earth system through absorbing and scattering solar radiation directly but also influence the cloud microphysical processes indirectly, and even the ecosystems at regional and global scales (Chen et al, ; Degobbi et al, ; DeMott et al, ; Jickells et al, ; Mahowald et al, ; Miller et al, ; Rosenfeld & Nirel, ). East Asia is a major source of dust aerosol as there are several deserts located in northwestern China and Mongolia that contribute a large amount of dust particles to the global dust mass loading (e.g., Chen et al, ; Guan et al, ; Hara et al, ; Huang et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…The relatively high (low) precipitation over the Huang-Huai (Yangtze) River basin from 2000 to 2008 in comparison with 1979-1999 is triggered by the transition from the warm to cold phase of the PDO around the 2000s, which is attributed to the weakened westerly winds and warming over Lake Baikal induced by a negative PDO phase after the 2000s (Zhu et al, 2011). The possible modulation of the PDO on the East Asian summer monsoon (EASM) and East Asian winter monsoon (EAWM), which are associated with summer and winter rainfall changes in eastern China, respectively, has been documented in previous studies (e.g., Yu, 2013;Chen et al, 2013). Zhou et al (2013) pointed out an anti-correlation between the PDO and EASM since the 1950s, and negative phases of the PDO correspond to a stronger EASM with more precipitation events over northern China.…”
Section: Introductionmentioning
confidence: 64%
“…Zhou et al (2013) pointed out an anti-correlation between the PDO and EASM since the 1950s, and negative phases of the PDO correspond to a stronger EASM with more precipitation events over northern China. A much stronger EASM tends to appear after a weak EAWM in positive phases of the PDO than in negative phases of the PDO (Chen et al, 2013). Existing studies also reported a similar relationship between the positive phase of the PDO and dryness in northern China and revealed that a warm phase of the PDO in 1976-1977 resulted in a weakened EASM associated with aridity in northern China in the 1980s and 1990s (Qian and Zhou, 2014;Zhu et al, 2015;Yang et al, 2017b;.…”
Section: Introductionmentioning
confidence: 69%
“…Dust particles, also called dust aerosols, are suspended in the atmosphere and are the main component of atmospheric aerosols, the aerodynamic diameter of which is usually less than 100 μm. The dust aerosols can modulate the cloud microphysical processes indirectly by acting as cloud condensation nuclei and ice nucleating particles (Mahowald et al 2007, Huang et al 2009, Mahowald et al 2010, Rodríguez et al 2012, Huang et al 2014, Nabat et al 2014, Chen et al 2014a, Kok et al 2023. The dust aerosols especially in East Asia have substantial impacts on human health, environment, ecosystems and climate (Abuduwaili et al 2010, Lin et al 2012, Huang et al 2013, Miao et al 2015, Schepanski 2018, Guo et al 2017.…”
Section: Introductionmentioning
confidence: 99%